2008
DOI: 10.1007/s10495-008-0242-5
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin protects auditory cells against cisplatin-induced death

Abstract: Cisplatin, a chemotherapeutic drug that is widely used to treat various cancers, promotes ototoxicity at higher doses. In this study, the effect of epicatechin (EC) on cisplatin-induced hair cell death was investigated in a cochlear organ of Corti-derived cell line, HEI-OC1, and in vivo in zebrafish. Cisplatin promoted apoptosis and altered mitochondrial membrane potential (MMP) in HEI-OC1 cells. EC inhibited cisplatin-induced apoptosis and intracellular reactive oxygen species (ROS) generation. Labeling of ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…This may be explained by synergistic effects of combinations of different green tea catechins on cell growth and apoptosis [35]. EC had almost no effect on cell growth or the induction of apoptosis [35,36], but a significant synergistic effect on the induction of apoptosis was observed when EC was combined with other catechins. Furthermore, Horie et al [35] found that catalase specifically canceled the synergistic effects of EC and EGCG, suggesting that the synergism involved production of reactive oxidative species, such as hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by synergistic effects of combinations of different green tea catechins on cell growth and apoptosis [35]. EC had almost no effect on cell growth or the induction of apoptosis [35,36], but a significant synergistic effect on the induction of apoptosis was observed when EC was combined with other catechins. Furthermore, Horie et al [35] found that catalase specifically canceled the synergistic effects of EC and EGCG, suggesting that the synergism involved production of reactive oxidative species, such as hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…In a our previous study from this laboratory, we investigated EC, a minor component of green tea, was investigated for its ability to prevent cisplatin-induced ototoxicity caused by ROS generation and by preventing changes in the MMP (Kim et al, 2008). Tea contains many known antioxidants and is one of the most popular beverages worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we investigated epicatechin (EC), a minor component of green tea, to determine whether it could be used to prevent cisplatin-induced ototoxicity caused by ROS generation, by preventing changes in the mitochondrial membrane potential (Kim et al, 2008). However, the molecular mechanism and in vivo functional studies of EC, as a chemopreventive agent, preventing cisplatin ototoxicity have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we investigated epicatechin (EC), a minor component of green tea, as a factor that prevented cisplatin-induced ototoxicity caused by ROS generation as well as changes in the mitochondrial membrane potential (MMP) (Kim et al, 2008). However, the function and mechanism of EC as a radioprotective agent against radiation-induced ototoxicity has not yet been investigated.…”
mentioning
confidence: 99%